2019
DOI: 10.1016/j.tsep.2018.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Energy and exergy analysis of fuel cells: A review

Abstract: In this paper, the fundamental overview of theoretical and practical aspects of thermodynamics analysis for mainly used fuel cells (FCs) are presented. The FC converts the chemical energy of fuel (normally hydrogen) directly into electrical energy resulting heat and liquid water as a waste products. In first part, governing equation of mass, energy, entropy and exergy are presented according to first law of thermodynamics (FLT) and second law of thermodynamics (SLT), more specifically energy and exergy analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(79 citation statements)
references
References 54 publications
0
70
1
8
Order By: Relevance
“…Owing to limited resources of fossil fuels with high demand is the major cause for researchers to develop environment-friendly power generating devices [1]. The fuel cell device produces energy without any toxic emissions to the environment and it has a wide variety of applications such as a power source for mobile applications and stationary devices [2,3]. Microfluidic fuel cells (MFCs) are one of the most recently developed and investigated micro fuel cell device which has created interest among the researchers these days for further studies due to its possible potential uses in portable electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to limited resources of fossil fuels with high demand is the major cause for researchers to develop environment-friendly power generating devices [1]. The fuel cell device produces energy without any toxic emissions to the environment and it has a wide variety of applications such as a power source for mobile applications and stationary devices [2,3]. Microfluidic fuel cells (MFCs) are one of the most recently developed and investigated micro fuel cell device which has created interest among the researchers these days for further studies due to its possible potential uses in portable electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…From the mathematical expressions described by equations (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), it is obviously noticed that the operation and performance characteristics of the PEMFC stack system are originally depended on a number of parameters. A part of these parameters are not available in the datasheet of the manufacturer and have to be carefully estimated to guarantee an accurate representation of the PEMFC, which gives results that match with experimental data.…”
Section: Objective Functionmentioning
confidence: 99%
“…Due to its sufficient way to obtain optimum solutions for complicated problems, Metaheuristics can be adapted to provide robust parameter estimation for fuel cell modeling. From this fact, the no-freelunch theorem has made a cogent remark that is employed by several optimization techniques to solve various engineering optimization problems [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…SOFCs are suitable for moderate-and high-power loads from 10 kW to 10 MW and exhibit the advantage of high conversion efficiency. Additionally, one review conducted energy and exergy analyses on various fuel cell types [57]. A theoretical analysis indicated that PEMFCs constitute a promising electrochemical energy conversion device for light-duty applications and have a maximum temperature of 90 • C, thus rendering them suitable for use in applications such as automobiles, buildings, electronics, and rechargeable batteries.…”
Section: Technology Review Of Fuel Cellsmentioning
confidence: 99%